PTH-058 Trainee Colonoscopists Acquire Competency at Different Rates, as Determined by Cusum Analysis Of Colonoscopy Data From The Jets Database. (4th June 2013) - Ward, S T; Mohammed, M A; Ismail, T; Valori, R; Dunckley, P
Abstract : Introduction: The number of colonoscopies required to reach competency is not well established. Nevertheless, a minimal number forms part of UK certification criteria. The Cusum technique is a statistical analysis of sequential data to determine if a process is 'in control'. The Joint Advisory Group on GI Endoscopy have developed an e-portfolio for users to record their endoscopic experience. The primary aim of this study was to determine the range of experience required by individuals to attain a caecal intubation rate (CIR) ≥90%, as defined by Cusum. A secondary aim was to assess which training factors are associated with attaining competence. Methods: Inclusion criteria were all e-portfolio users who had performed ≤50 ('baseline') colonoscopies prior to submission of data to the e-portfolio; termed 'trainees'. All colonoscopy records for the trainees were retrieved from the e-portfolio database and learning curve-Cusum analysis was performed. This analysis of colonoscopy completion reports the number of procedures required for CIR performance to reach ≥90%. A colonoscopy was defined complete if the caecum or ileum was reached and was performed without assistance. Trainees who had attained a CIR≥90% were compared to those with a CIR < 90% for differences in previous endoscopic experience, case volume and other trainee factors by univariate (Mann-Whitney, Chi-squared) and multivariate (binomial logistic regression) analysis. Results: The e-portfolio contained 169, 515 colonoscopy records entered by 1, 572 different users. 265 users ('trainees') were confirmed to have performed ≤50 baseline colonoscopies and were included in subsequent analyses. By Cusum method, 39 trainees attained a CIR≥90%; 226 achieved a CIR < 90%. For those trainees with over 250 procedures, only 47% attained a CIR≥90%. Factors associated with attaining CIR≥90% were high number of procedures (P < 0.01), high number of colonoscopies per month (P < 0.01), and prior experience of more than 100 sigmoidoscopies (P = 0.017) by univariate and multivariate analysis. Nurse endoscopists attained competency at a higher rate than gastroenterology or surgical trainees by univariate (P = 0.01) but not multivariate analysis. Conclusion: This is the largest study to date by both procedure and trainee numbers assessing colonoscopy competency by Cusum method. Trainees achieve competency at different rates. A high proportion of trainees will not attain a CIR > 90% even after 250 procedures. High case volume and prior sigmoidoscopy experience are associated with a CIR > 90%. The potential of both these factors to influence the attainment of competency should be exploited within endoscopy training programmes. Disclosure of Interest: None Declared.